Flash Flood Risk and Climate Analysis in the Extreme South of Algeria (the Case of In-Guezzam City) - Zegait, Rachid; Şen, Zekai; Pulido-Bosch, Antonio; Madi, Housseyn; Hamadeha, Bachir (Geomatics and Environmental Engineering, 2022)
Natural risks, particularly flood risk, are a topical subject in Algeria and throughout the world, particularly given the last major catastrophic floods in Sudan (2020) and North Africa. With the development of the climate change phenomenon in the world, risk management is becoming increasingly necessary for all the actors concerned (decision-makers, technicians, and the population) to identify protection issues. In 2018, in the extreme south of Algeria, In-Guezzam City suffered a devastating flood that caused significant damage and loss of human and material resources. More than 100 homes collapsed, and approximately 345 families were displaced. Currently, there is no research work to assess the hydrological situation and the risk of flooding in this region. Therefore, the main purpose of this study is to shed light on the risk of flash floods in the extreme south of Algeria with more specific attention to the August 2018 floods as well as the climate trends over the past 30 years using Mann–Kendall test and Sen’s Slope Estimator. The chosen approach involves a hydrological study and hydrodynamic modeling using HEC-RAS software. This latter allows for simulating floods using statistical methods and creating several regional flood hazard maps.